2017
DOI: 10.1080/14767058.2017.1293034
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for fatality in amniotic fluid embolism: a systematic review and analysis of a data pool

Abstract: Further research on national registries should focus on the behaviour of oxytocin infusion during labour in AFE cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…A study of 227 cases ascertained from a coded national hospital admissions database and a study of just 20 cases ascertained from a regional database with additional criteria to exclude false positive cases both found no significant association between various sociodemographic or obstetric-related characteristics and fatality [9,36]. A study that reviewed 44 case reports of AFE found that treatment with factor VIIa was associated with an increased risk of death or permanent disability, while a recent study that reviewed 177 case reports of AFE only found a significant association between oxytocin use during labour and fatality amongst typical cases of AFE defined as having the classical triad of symptoms (cardiac arrest/cardiovascular collapse, respiratory failure, coagulopathy) [37,38]. Another study of 180 cases identified from a coded hospital admissions population database found a crude association between induction of labour and fatality [9].…”
Section: Discussionmentioning
confidence: 99%
“…A study of 227 cases ascertained from a coded national hospital admissions database and a study of just 20 cases ascertained from a regional database with additional criteria to exclude false positive cases both found no significant association between various sociodemographic or obstetric-related characteristics and fatality [9,36]. A study that reviewed 44 case reports of AFE found that treatment with factor VIIa was associated with an increased risk of death or permanent disability, while a recent study that reviewed 177 case reports of AFE only found a significant association between oxytocin use during labour and fatality amongst typical cases of AFE defined as having the classical triad of symptoms (cardiac arrest/cardiovascular collapse, respiratory failure, coagulopathy) [37,38]. Another study of 180 cases identified from a coded hospital admissions population database found a crude association between induction of labour and fatality [9].…”
Section: Discussionmentioning
confidence: 99%
“…[1,9] Other risk factors that may be associated with AFE include the use of oxytocin, cervical lacerations, uterine rupture, eclampsia, polyhydramnios, and multiple birth. [10][11][12] With amniotic fluid or fetal materials entering the maternal circulation, the pulmonary vessels experience spasms. Hypoxia and decreased left ventricular function occur as a result of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The challenges of childbirth, especially when they involve long -term use of oxytocin or a combination of oxytocin and prostaglandins, increase the risk of amniotic fluid embolism [16]. Recently, Indraccolo and colleagues, analyzing the results of a systematic review of amniotic fluid embolism cases from 1990 to 2015 showed that only the injection of oxytocin during the course of labor statistically significantly increases the risk of developing the syndrome [17].…”
Section: Pathogenesismentioning
confidence: 99%